Conhecimento, atitudes e práticas contraceptivas de mães adolescentes. - SILVA, Mariana Morgana Sousa e (2021)
Teenage pregnancy is a public health problem with repercussions for women, children, families and society. This study aimed to identify the knowledge, attitudes and contraceptive practices of adolescent mothers. Cross-sectional, descriptive, exploratory study through the application of a CAP survey with a quantitative approach carried out in four maternity hospitals in the metropolitan region of São Luís-MA from October 2020 to January 2021. The sample consisted of 163 teenage mothers who were hospitalized in the rooming-in of selected maternity hospitals. The age of the interviewees ranged from 14 to 19 years old, with more frequency between 18 and 19 years old (52.15%). Most puerperal women had a family income of up to one minimum wage, had not completed high school and had interrupted their studies, mostly motivated by the occurrence of pregnancy. In general, inadequate knowledge, attitudes and contraceptive practices were observed among adolescents with a higher rate of error in the dimension of contraceptive practice (98.78%). Contraceptive knowledge and attitude was adequately observed in 14.11% and 7.98% of postpartum women, respectively. The lack of knowledge of adolescent mothers was highlighted, especially regarding the use of oral contraceptives. The use of contraceptive methods before the current pregnancy and the contraceptive attitude of the adolescent mothers were associated with the contraceptive practices of the sample (p-value < 0.05). The family and the school are considered support networks that can help guide adolescents on contraceptive methods. The health professional, especially the nurse, has a fundamental role in the reception, guidance and empowerment of adolescents on the available forms of contraception, in order to promote the proper use of contraceptives from the first sexual intercourse or the prevention of a second pregnancy unplanned.